LOADING PREMI KOTOR TAHUNAN DENGAN HUKUM DE MOIVRE PADA ASURANSI JIWA BERJANGKA - Shelvyana, Ryska; ', Hasriati; Nababan, Tumpal Parulian (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the calculation of the loading annual gross premium with De Moivre’s law at term life insurance. In insurance the loading is obtained by substracting net premium from gross premium. Loading is affected by a singlepremium, present value of annuity, annual premium payment with k times a year using the De Moivre’s law.